Automatic GPR detection of grouting defects behind the tunnel shield segments based on wavelet coherence analysis combined with modified Res-RCNN - Dengyi Wang; Ming Peng; Liu Liu; Xiongyao Xie; Zhenming Shi; Yaoying Liang; Jian Shen; Qiyu Wu (Case Studies in Construction Materials)
Ground penetrating radar (GPR), a widely used non-destructive testing technique for detecting grouting defects behind tunnel shield segments, faces challenges like steel rebar interference, low working efficiency, and expert interpretation reliance. To address these, this paper introduces an automated approach using wavelet coherence and a modified Res-RCNN. The approach employs wavelet coherence to transform the time-series GPR profile into the time-frequency images and reveal the weak defect reflections. Then, a modified Res-RCNN is applied to automatically extract the defect features from the wavelet coherence images. Finally, the post-processing and visualization automatically give an intuitive clear feature map that shows the location and probability of the grouting defects along the tunnel. The proposed methods are verified through full-size model tests with the aid of synthetic experiments to quantify their performance. The results show that wavelet coherence analysis improves the visibility of weak signals in (GPR) profiles, enabling their identification in the time-frequency domain by leveraging local coherence between adjacent signals and using phase information. The wavelet coherence analysis enables the observation of grouting defects behind tunnel shield segments with interferences of steel rebars. It can be applied even when the defect reflection is very weak, such as when the SNR is less than −40 dBs. The modified multi-task Res-RCNN, combined with post-processing and visualization, generates defect features including location and probability of existence. The network demonstrates superior training convergence and prediction accuracy due to information sharing between different task heads, compared to a two-classification network with the same Res-Net backbone. Through quantitative experiments in both model and synthetic tests, we recommend a trace interval of 15 to avoid the high coherence amplitude caused by two reflections out of same individual rebar.